Introducing New Methods of Electroprocessing in Meat and Meat Products - Sarwary, Nasir Ahmad (Journal of Natural Sciences – Kabul University, 2023)
Meat spoils quickly, and preserving it for extended periods without undesirable changes is challenging using traditional methods. However, newer technologies allow for longer and better-quality preservation. Electroprocessing technologies, such as Electrical Stimulation (ES) and Pulsed Electric Fields (PEF), have seen significant advancements in recent years. These non-thermal methods do not primarily rely on increased temperature but instead focus on the electric fields. Electrical stimulation is an established technique in meat processing, while microwave and radio frequency heating are commercially successful for tempering, defrosting, and cooking meats. Ohmic heating is expected to become more widely applicable in the future, as it is a lower-cost and more energy-efficient alternative to microwave and radio frequency technologies.